Ο ΗΡΑΚΛΗΣ, ΟΙ ΑΜΑΖΟΝΕΣ ΚΑΙ ΟΙ «ΤΡΑΓΑΝΙΣΤΕΣ ΒΟΥΚΙΤΣΕΣ». ΑΝΑΠΑΡΑΣΤΑΣΕΙΣ ΤΟΥ ΦΥΛΟΥ ΚΑΙ ΤΗΣ ΕΞΟΥΣΙΑΣ ΣΤΟ ΕΡΓΟ ΤΟΥ ΡΗΓΑ - ΛΙΑΚΟΣ, ΑΝΤΩΝΗΣ (Μνήμων, 2001)
Antonis Liakos, Hercules, Amazons and the delicious crumpets. Representationsof Gender and Power in the Writings of Rigas This paper explores the question why the well-known intellectual andpatriot Rigas Ferraios had used in his monumental Carta the image ofHercules fighting an Amazon. What were the sexual connotations ofthis representation in a map intended to represent the space of thenation? The central idea is that the representations of masculinity andnationality were tightly interconnected, and through this interconnectionboth were redefined.